Kodifikasi Hadith Sunni dan Syi’ah - Abd Majid Abror (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
There is a fundamental difference when we compare the codification of the Qur'an with the history of the development of hadith. where, hadith is widely narrated on Sunday, individually, books by Sunni scholars on the situation and circumstances of the history of travel and the development of hadith from its growth to the present, it can be concluded that hadith has gone through seven periods, and has now entered a period of seven. In the Shia tradition, hadith writing has actually existed since its inception. At the time of the prohibition of hadith, in the history of Shi'ite has never experienced stagnation and continues to. Until the time of codification and preparation of The Shia Hadith, more quoting and copying the writings in the appeal leaned on oral entry. If we compare the development of Hadith in both groups, we find that the Shia Hadith itself is actually not as complicated and complex as it is in the Sunni tradition. This is due to the Shia system that has long been writing hadith since the beginning of Islam. In addition, there are also differences of views between the two groups regarding the hadith itself. The source of hadith according to Shiites is not only the prophet Muhammad, but every imam who ma'shum can also issue hadiths that are used as arguments.